Infuence of mariculture on the distribution of dissolved inorganic selenium in Sanggou Bay, northern China - Y Chang (Inter-Research, 2016)
Selenium is known as a ‘double-edged sword’ element on account of its dual beneficial and toxic effects on organisms, depending on its concentration and chemical form. Dissolved inorganic selenium (DISe) concentration in the water column and selenium content in biological species were investigated in a typical aquacultural area in Sanggou Bay, China. In addition to sampling within Sanggou Bay, the main sources of DISe into Sanggou Bay were sampled to estimate selenium transport from different sources. Results showed that DISe and selenite [Se(IV)] concentrations averaged, respectively, 0.69 nmol l-1 and 0.28 nmol l-1, with ranges 0.21 to 1.36 nmol l-1 and 0.07 to 0.58 nmol l-1, in the surface water of Sanggou Bay. The DISe in Sanggou Bay remained well below the toxic levels. The DISe and Se(IV) concentrations varied temporally, with lows in summer and highs in spring and autumn. Concentrations showed strong horizontal gradients from the coast to offshore areas within the bay, as significantly influenced by the intensive and widespread seaweeds and bivalves aquaculture activity in the bay. The highest selenium content (mean ± SD) was observed in scallops (3.6 ± 0.7 µg g-1), followed by oyster (1.6 ± 0.4 µg g-1), phytoplankton (0.9 ± 0.3 µg g-1), Gracilaria lemaneiformis (0.063 ± 0.008 µg g-1) and kelp (0.032 ± 0.005 µg g-1). The main source of DISe in Sanggou Bay was water exchange with the Yellow Sea, whereas the most important sink was biological activity, which removed 53 ± 12% of the incoming selenium from bay waters.